2018
DOI: 10.2298/vsp160226321p
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apically extruded debris during removal of gutta-percha and ResilonTM using different instrumentation techniques

Abstract: Background/Aim. Apical extrusion of material is considered as one of the very important factor for endodontic treatment success. Microorganisms, necrotic tissue, filling material and irrigants, which can be extruded apically during endodontic retreatment, may jeopardize the success of the therapy. The aim of this in vitro study was to quantitatively evaluate the amount of apically extruded debris during endodontic retreatment of teeth obturated with two different materials, using one hand and three rotary inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 23 publications
2
3
0
5
Order By: Relevance
“…This study evaluated three different instruments (Hedstrom, ProTaper and Twisted File) during retreatment and their impact on apically extruded material. The present study showed that in vitro, all of the tested instruments produced apical extrusion of obturation material and these results are consistent with other apical extrusion studies [7,11,12,14,16,18]. As already mentioned, no studies are present in the current literature on the apical extrusion during retreatment with Twisted File instruments.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study evaluated three different instruments (Hedstrom, ProTaper and Twisted File) during retreatment and their impact on apically extruded material. The present study showed that in vitro, all of the tested instruments produced apical extrusion of obturation material and these results are consistent with other apical extrusion studies [7,11,12,14,16,18]. As already mentioned, no studies are present in the current literature on the apical extrusion during retreatment with Twisted File instruments.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study the highest mean score of extruded material during retreatment was observed in the manual Hedstrom group and the lowest when Twisted File rotary instruments were used. The results of the present study are in agreement with previous retreatment studies that also compared hand and engine-driven instruments and their impact on apical extrusion [7,12,14,16,17]. This could be explained with rotation and a crown-down preparation technique during instrumentation, which tends to pull dentinal debris into the flutes of the file and direct it toward the coronal part of the canal [3,19].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations